2018
DOI: 10.1101/332346
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploiting Index Cross-Talk to Modify Variant Calls

Abstract: Modern next-generation DNA sequencers support multiplex sequencing to improve throughput and decrease costs. This is done by pooling and sequencing samples together in parallel, which are later demultiplexed according to their unique indexes 1, 2 . When reads are assigned to the wrong index, called index cross-talk, information is leaked between samples 3-6 . This creates a physical information side-channel, a well known class of vulnerabilities in information security [7][8][9][10] , that may be used to modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This increasing integration and dependence on the digital space (for example, computer-controlled instruments within biomanufacturing processes) creates a new category of risks between cyber and biological systems. Cyber-biocrime describes criminal activities carried out by combined means of computers/Internet and biological/biochemical material, and was discussed in six studies (Ney et al, 2017 , 2018 ; Wintle et al, 2017 ; Peccoud et al, 2018 ; Faezi et al, 2019 ; Qu, 2019 ). Peccoud et al introduce the need for “cyberbiosecurity” to prevent (for example) the manufacture of nefarious products through the tampering of electronic orders of DNA sequences or the interception of shipments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This increasing integration and dependence on the digital space (for example, computer-controlled instruments within biomanufacturing processes) creates a new category of risks between cyber and biological systems. Cyber-biocrime describes criminal activities carried out by combined means of computers/Internet and biological/biochemical material, and was discussed in six studies (Ney et al, 2017 , 2018 ; Wintle et al, 2017 ; Peccoud et al, 2018 ; Faezi et al, 2019 ; Qu, 2019 ). Peccoud et al introduce the need for “cyberbiosecurity” to prevent (for example) the manufacture of nefarious products through the tampering of electronic orders of DNA sequences or the interception of shipments.…”
Section: Resultsmentioning
confidence: 99%
“…Ney et al ( 2018 ) demonstrated targeted “mis-genotyping,” where a healthy DNA sample may be misclassified as one (in their example) with anemia ( Figure 5 , Table 2 , Supplementary Table 1 ). This was achieved by a physical side channel attack on modern next-generation DNA sequencers (NGS) that are capable of sequencing multiple sequences at once to increase throughput.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the increased reliance of the bioscience fields on cyberphysical systems (CPS, Fig. 3 below), potentials for exploitation exist at each point where bioengineered or biomanufactured processes or services interface with the cyber and the physical domain, whereby attackers may exploit unsecured networks and remotely manipulate biologic data, exploit biologic agents, or affect physical processing involving biological materials, that result (whether intentionally or unintentionally) in unwanted or dangerous biological outcomes [ [4] , [5] , [6] , [7] ].
Fig.
…”
Section: Motivationmentioning
confidence: 99%